2011
DOI: 10.1007/s12355-011-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Ammi Analysis and its Application to Sugarcane Regional Trials in Venezuela

Abstract: The problem of genotype by environment interaction (G 9 E) is that often complicates the interpretation of trials in multiple locations, making it difficult to select genotypes adapted to different environments. AMMI model was adopted to analyze ten sugarcane genotypes in ten Venezuelan environments evaluated through two years of cultivation. The objectives of this study were to identify stable and adaptable genotypes in different locations and determine the magnitude of G 9 E interaction. The analysis of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…5). Similar results obtained by Bissessur et al (2001), Jun et al (2009, Rea et al (2011), Tiawari et al (2011), Imtiaz et al (2013, Guddadamath et al (2014) and Rajesh and Sinha (2015).…”
Section: B4-brixsupporting
confidence: 84%
See 1 more Smart Citation
“…5). Similar results obtained by Bissessur et al (2001), Jun et al (2009, Rea et al (2011), Tiawari et al (2011), Imtiaz et al (2013, Guddadamath et al (2014) and Rajesh and Sinha (2015).…”
Section: B4-brixsupporting
confidence: 84%
“…The other genotypes were unstable (S2di gave highly significant from zero). Similar results obtained by Bissessur et al (2001), , Jun et al (2009, Rea et al (2011), Tiawari et al (2011), Dutra et al (2014), Jun et al (2014, Rea et al (2015), Anand et al (2016) and Prema et al (2017). Klomsa et al (2013) noticed that the genotype K88-92 was the most superior genotype in cane yield.…”
Section: B3-cane Yieldsupporting
confidence: 81%
“…Among the most common methods are linear regression analysis, non-linear regression analysis, multivariate analysis and non-parametric statistics (Cornelius et al, 1996;Annicchiarico, 1997;Moreno-González et al, 2004). In recent years, the quantification of G × E interactions and yield stability studies involving sugarcane have been done through multivariate procedures, such as principal component analysis (Kumar et al, 2009;Guerra et al, 2009;Rea et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding specific adaptability, the positive interaction between the genotypes G10 and G11 with the environment E6 can be highlighted. Rea et al (2011) reported that i) vectors of the environment with angles smaller than 90° indicate environments with a similar influence on genotypes; ii) angles close to 90° indicate no correlation between the environments; and iii) angles close to 180° indicate a strong opposite relationship. However, as the objective of the study was to identify strong associations in the distinction of the genotypes, environments with angles of up to approximately 25° were considered similar.…”
Section: Resultsmentioning
confidence: 99%